Exploring the use of artificial intelligence in Indonesian accounting classes - Fachrurrozie Fachrurrozie; Ahmad Nurkhin; Jarot Tri Bowo Santoso; Hasan Mukhibad; Christian Wiradendi Wolor (Cogent Education)
This study aims to reveal the use of artificial intelligence (AI) in accounting classes, analyze the factors that influence educators to use AI continuously in learning, and describe the challenges and ethics in developing AI. The research population is accounting educators (teachers and lecturers) in Indonesia who are members of the Professional Alliance of Accounting Educators throughout Indonesia. The sampling method used was purposive sampling. The data collection method was a questionnaire distributed online via the Google form platform, which gathered 230 responses, including 146 teachers and 84 lecturers. The descriptive analysis method and structural equation model analysis were used to analyze the research data. The findings show that Canva is the most widely used AI tool, followed by ChatGPT. Teachers and lecturers use AI primarily to create learning materials and write academic articles. The structural equation model analysis results reveal that only performance expectancy and gender significantly impact the intention to use AI in accounting education. Conversely, competence and intention are the key factors significantly affecting actual AI usage behavior in accounting learning. In addition, various challenges exist in developing and using AI, including issues related to effectiveness and efficiency, IT ethics, and fostering student engagement and interaction.